1976
DOI: 10.1002/jbm.820100109
|View full text |Cite
|
Sign up to set email alerts
|

Hair sampling for chromium content following Charnley hip arthroplasty

Abstract: The chromium content of hair has been studied by neutron activation analysis of samples from 62 patients following a Charnley unilateral or bilateral hip arthroplasty by an artificial joint of stainless steel against polyethylene, inserted three to five years previously. The patients lived in the North Wales area of the British Isles. Hair chromium content was also studied in 51 control subjects of similar age to that of the patients, from the same geographical area and often from the patients' own households.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The release of metal ions following the implantation of a metallic device has been a well recognised phenomenon in orthopaedics for over fifty years now (1-3). Various studies have shown raised levels of metal ions including titanium, nickel, cobalt and chromium in serum, blood clot and urine samples after implantation with alloys containing these metals (4-6).…”
Section: Introductionmentioning
confidence: 99%
“…The release of metal ions following the implantation of a metallic device has been a well recognised phenomenon in orthopaedics for over fifty years now (1-3). Various studies have shown raised levels of metal ions including titanium, nickel, cobalt and chromium in serum, blood clot and urine samples after implantation with alloys containing these metals (4-6).…”
Section: Introductionmentioning
confidence: 99%